Quality of life of alcohol dependent patients attending a deaddiction centre in Kannur district - Ratheesh, R.; Mohandas, Bindu; Venugopalan, P. P.; Sarada, A. K.; K., Suprej; V. K., Sobith (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Quality of life (QOL) is individuals’ perceptions of their position in life. QOL of alcohol dependent patients is an area that has received relatively less attention compared to other alcohol related problems. Methods: A deaddiction centre based cross sectional study was done on 370 individuals using a predesigned questionnaire during the period of 2012-2013. The data was analyzed using SPSS version 17. Spearman’s rank correlation test was used to find association between the study variables. Results: The mean age of the study subjects was 38.08±8.46 years. The mean duration of drinking was 12.62±7.47 years. The overall score of the QOL and the perceived health in alcohol dependent patients was 3.19±0.89 and 3.01±0.98 respectively. The mean of the transformed scores of physical, psychological, social and environmental domains are 69.12±12.82, 57.84±12.81, 58.52±17.05, 68.62±10.23 respectively. Statistical analysis of age with physical, environmental and social domains showed a significant negative correlation; literacy status with QOL, perceived health, physical, psychological, social and environmental domains showed a significant positive correlation; socio economic status with QOL and psychological domain showed a significant positive correlation; duration of drinking with QOL, perceived health, physical and psychological domain showed a significant negative correlation. Conclusions: Harm from alcohol use is a major public health problem. Reducing the level of social and health harms from alcohol requires preparation and planning.